Chemical Profile, In Vitro Antioxidant, Pancreatic Lipase, and Alpha-Amylase Inhibition Assays of the Aqueous Extract of Elettaria cardamomum L. Fruits - Hanan M. Al-Yousef; Ali S. Alqahtani; Wafaa H. B. Hassan; Afraa Alzoubi; Sahar Abdelaziz (Journal of Chemistry)
Phytochemical and pharmacological investigations of Elettaria cardamomum L. were mostly focused on its essential oil and organic crude extracts with little attention on its aqueous extracts. Therefore, the current study aimed to investigate the phytochemical profile, in vitro antiobesity, and antidiabetic activities of the aqueous extract of Elettaria cardamomum L. family Zingiberaceae. UPLC-ESI-MS/MS analysis is used for the aqueous extract characterization in both ionization modes. The analysis revealed the tentative identification of forty-seven compounds based on their MS/MS fragmentation pattern and comparison with the reported data. The identified compounds include eight flavones, thirteen phenolic and nonphenolic acids, one coumarin, and nineteen anthocyanins. Moreover, the in vitro antiobesity and antidiabetic activities were also studied. The results showed that E. cardamomum L. aqueous extract inhibits pancreatic lipase and α-amylase enzyme in a concentration-dependent manner, as 1 mg/mL extract was able to inhibit pancreatic lipase and α-amylase by 62.25% ± 0.58 (IC50 = 288.75 ± 1.3 µg/mL) and 70.42% ± 1.5 (IC50 = 220.5 ± 1.3 µg/mL), respectively. Conclusively, the current study indicated that the investigated biological activities of Elettaria cardamomum aqueous extract were attributed to the existence of biologically active metabolites such as flavones, phenolic and nonphenolic acids, coumarins, and anthocyanins. Moreover, it proposed that the aqueous cardamom extract can be used as a natural potential source in different pharmaceutical preparations to protect against variable chronic disorders, especially obesity and diabetes. Deeper in vivo investigations, isolation, purification, and structural elucidation of the major active metabolites from cardamom are recommended.